Three-Year Follow-Up of Posterior Chamber Toric Phakic Intraocular Lens Implantation for Moderate to High Myopic Astigmatism - Kamiya, Kazutaka (Public Library of Science, 2013)
PURPOSE: To assess the 3-year clinical outcomes of toric phakic intraocular lens (Visian ICL™; STAAR Surgical) implantation for moderate to high myopic astigmatism. METHODS: This retrospective study evaluated fifty eyes of 28 patients who underwent toric ICL implantation for the correction of moderate to high myopic astigmatism and who regularly returned for postoperative examination. Before, and 1, 3, and 6 months after, and 1, 2, and 3 years after surgery, we assessed the safety, efficacy, predictability, stability, and adverse events of the surgery in eyes undergoing toric ICL implantation. RESULTS: The logarithm of the minimal angle of resolution (LogMAR) uncorrected visual acuity and LogMAR best spectacle-corrected visual acuity were –0.10 (corresponding to Snellen equivalents 20/16) ± 0.16 and –0.20 (corresponding to 20/12.5) ± 0.07, 3 years postoperatively, respectively. The safety and efficacy indices were 1.16 ± 0.20 and 0.94 ± 0.28. At 3 year, 82% and 98% of the eyes were within 0.5 and 1.0 D, respectively, of the targeted correction. Manifest refraction changes of –0.15 ± 0.31 D occurred from 1 month to 3 year. No vision-threatening complications occurred during the observation period. CONCLUSIONS: On the basis of the clinical results of this study, toric ICL implantation was good in all measures of safety, efficacy, predictability, and stability for the correction of moderate to high myopic astigmatism throughout a 3-year observation period.